The ranked species occupancy curves reflect the dominant process of species sorting: Evidence from forest/scrub communities. (23rd October 2021) - Gafta, Dan; Stoica, Ilie‐Adrian; Coldea, Gheorghe
Abstract: Questions: Abiotic filtering, competitive interactions and niche pre‐emption effects, as important drivers of the species sorting in plant communities, were hypothesised to be responsible for the amount of concavity and shoulder distinction in ranked species occupancy curves (RSOCs). In connection with the intermediate productivity hypothesis, we proposed an adjustment and extension of the RSOC models concerning the ecological mechanisms underlying their shaping. We aimed at estimating the effects of the variation in resource availability and functional species composition on the RSOCs of 30 woody vegetation syntaxa. Location: Low plains to the subalpine belt (southeastern Carpathians) throughout Romania. Methods: The fraction of vascular plant species with either low (< 3) or large (>7) Ellenberg ecological indicator values were used as proxies for abiotic variables. Both the standardised effect size of homotoneity (SES‐h, estimated by contrasting empirical vs null RSOCs) and the regression parameters of the fitted RSOCs were used, after adjusting them for differences in sampling scale, as shape descriptors. Results: The empirical RSOCs were all fitted best by the power exponential function. With increasing fraction of ruderal species and canopy openness, the slopes of RSOC's heads became gentler (larger power parameter). Higher levels of soil fertility towards lower elevations translated in reduced concavity of the RSOCs (larger exponential parameter). Larger/smaller SES‐h were associated with richer/poorer habitat‐specific species pools that were ascribed to low‐elevation, open‐canopy vegetation (oak‐dominated forests, shiblyak woodlands, secondary scrubs) and, respectively, (sub)montane, closed‐canopy, mixed beech or spruce forests and sub‐alpine scrubs. Conclusions: Dense species packing and even niche partitioning in communities developed in moderately productive sites are associated with shoulder‐free, long‐tailed, slightly concave RSOCs. Conversely, strong filtering in stressful environments and/or low light availability under closed, woody canopies are related to steep, short‐tailed, exponential‐like RSOCs. The availability of resources and the equitability of niche partitioning, underlying the process of species sorting during plant community assembly, play a major role in shaping the RSOCs. Abstract : We provide indirect evidence of how variation in resource availability and niche partitioning can model the shape of the ranked species occupancy curves (RSOCs) in relatively homogeneous plant metacommunities (syntaxa). Dense species packing and evenness in moderately productive sites are associated with shoulder‐free, long‐tailed, slightly concave RSOCs. Strong species filtering under low nutrients and/or light availability are related to steep, short‐tailed, exponential‐like RSOCs. Meaningful plant functional traits should be considered to fully understand the ecological meaning of the RSOCs' shapes.